EXPLORING ENGLISH TEACHERS' BELIEFS ON THEIR TEACHING PROFESSION - Fajrinur Fajrinur (Universitas Islam Negeri Banda Aceh, 2019)
The aim of this study is to explain the influence of the English teachers’ beliefs toward their teaching profession in Bireuen District, Aceh Province. This is a quantitative study which involved thirty English teachers as the respondents. These teachers teach at six high schools in Bireuen. The schools were purposively selected to cover the broad area of Bireuen District. Some of the schools were in the rural area, some are in the city. Five English teachers from each high school were randomly selected. The data collection was done using questionnaires. It can be concluded from the answer that in general the teachers have positive beliefs toward their profession, they satisfied with their job, they feel confidence about their job, it can also be seen from the answers that most teachers received appraisal and feedback from other teachers and most of the teachers believe that appraisal and feedback can increase teaching passion. Beliefs about overall job-related principles, job satisfaction, self-efficacy and appraisal and feedback give big influence toward their teaching profession as English teachers. This big influence is affecting teachers is various way. Beliefs appear to have the strongest impact on teacher learning, followed by changes in teacher behavior and last on students learning.